PENERAPAN MANAJEMEN STRATEGIK DALAM MENINGKATKAN MUTU PENDIDIKAN MADRASAH - Wiwin Mistiani (Paedagogia: Jurnal Pendidikan, 2018)
In its development, madrasas have undergone various changes, namely from the pesantren learning system to the madrasa system; from traditional to classical methods; from halaqah system to benches, desks and blackboards; from traditional to modern curricula; from classical education to modern educational reform. the change indicates the existence of process or efforts of development of madrasah education in the direction of more advanced, qualified and competitive from time to time. Conceptually, one way to improve the quality of education and competitiveness of madrasah in the era of globalization competition is to implement strategic management which includes 4 stages such as environmental analysis, formulating, implementing and evaluating strategic decisions between functions that enable an organization to achieve its goals in the future. Strategic Management is based on the entire scope of the work. Thus it can be utilized well for makronya environment for example in government management and also can be utilized also for in mikronya environment for example in company management or organization or pengeloalan Madrasah. However, it should be understood only here that in the use of macro and micro scope there are a number of fundamental differences such as the following exposures.